Defect Detection on Texture using Statistical Approach - Siana Halim (Institute of Research and Community Outreach - Petra Christian University, 2015)
In this paper we present several techniques for detecting simple defect on the texture. The simple defect means, that the defect can be detected via image histogram or via wavelet of the image histogram. Hill estimator is one of the techniques that we suggest to use to solve this problem, since it does not need estimate parameters for estimating the image density